Evolution and expression of the duck TRIM gene repertoire - Campbell, Lee K.; Peery, Rhiannon M.; Magor, Katharine E. (Frontiers in Immunology, 2023)
Tripartite motif (TRIM) proteins are involved in development, innate immunity, and viral restriction. TRIM gene repertoires vary between species, likely due to diversification caused by selective pressures from pathogens; however, this has not been explored in birds. We mined a de novo assembled transcriptome for the TRIM gene repertoire of the domestic mallard duck (Anas platyrhynchos), a reservoir host of influenza A viruses. We found 57 TRIM genes in the duck, which represent all 12 subfamilies based on their C-terminal domains. Members of the C-IV subfamily with C-terminal PRY-SPRY domains are known to augment immune responses in mammals. We compared C-IV TRIM proteins between reptiles, birds, and mammals and show that many C-IV subfamily members have arisen independently in these lineages. A comparison of the MHC-linked C-IV TRIM genes reveals expansions in birds and reptiles. The TRIM25 locus with related innate receptor modifiers is adjacent to the MHC in reptile and marsupial genomes, suggesting the ancestral organization. Within the avian lineage, both the MHC and TRIM25 loci have undergone significant TRIM gene reorganizations and divergence, both hallmarks of pathogen-driven selection. To assess the expression of TRIM genes, we aligned RNA-seq reads from duck tissues. C-IV TRIMs had high relative expression in immune relevant sites such as the lung, spleen, kidney, and intestine, and low expression in immune privileged sites such as in the brain or gonads. Gene loss and gain in the evolution of the TRIM repertoire in birds suggests candidate immune genes and potential targets of viral subversion.